Relation between biophysical properties of nanostructures and their toxicity on zebrafish - Martinez, Carolina Soledad (2017)
In recent years, the use of commercial nanoparticles in different industry and health fields has increased exponentially. However, the uncontrolled application of nanoparticles might present a potential risk to the environment and health. Toxicity of these nanoparticles is usually evaluated by a fast screening assay in zebrafish (Danio rerio). The use of this vertebrate animal model has grown due to its small size, great adaptability, high fertilization rate and fast external development of transparent embryos. In this review, we describe the toxicity of different micro- and nanoparticles (carbon nanotubes, dendrimers, emulsions, liposomes, metal nanoparticles, and solid lipid nanoparticles) associated to their biophysical properties using this model. The main biophysical properties studied are size, charge and surface potential due to their impact on the environment and health effects. The review also discusses the correlation of the effects of the different nanoparticles on zebrafish. Special focus is made on morphological abnormalities, altered development and abnormal behavior. The last part of the review debates changes that should be made in future directions in order to improve the use of the zebrafish model to assess nanotoxicity.